CONFLICT RESOLUTION: THE DYNAMICS OF AGRARIAN CONFLICT SOLUTION BETWEEN HARJOKUNCARAN VILLAGERS AND TNI-AD (ARMY) IN MALANG - Haidar Fikri (Fakultas Hukum, Universitas Diponegoro, 2018)
Indonesia as state law has several problems which related to the various sector. Land is a sector where the conflict often occurs, so this problem had a very close relationship with the law. The land problems in Harjokuncaran village is not apart with farmer community life who fight for their land right.One form of resistance in Harjokuncaran village was the agrarian conflict that causing physical violence between TNI-AD (Army) and Harjokuncaran villagers. This study using social movement theory and conflict resolution, this theory was chosen to review about how to form farmers movement stage until its conflict resolution. The method used is a qualitative descriptive method as the data analysis form obtained in the field. The process to collect the data using: observation, literature study, interview, and documentation. The result showed that how the most important potential to bring up the movement as the result of complaint and disappointment faced by Harjokuncaran villagers. After the social movement occurred through this resistance, their existence had been recognized by Magelang Regency Government, therefore the government had tried as much as possible to give the best solution in order to create a peaceful life. In another word, there is a conflict resolution for this problem.